Adult acetabulo – pelvic parameters in Turkish society: A descriptive radiological study - Murat Aydin; Cihan Kircil; Onur Polat; Murat Arikan; Bülent Erdemli (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: The aim of this study was to measure the prevalences of the acetabular index, collodiaphyseal angle, CE angle, articulo-trochanteric distance, cross-over sign and posterior wall sign in healthy Turkish people, in order to shed light on the production of orthopedic medical products. Methods: In this study, both hips (a total of 3960 hips) of 1980 individuals (1178 males, 802 females) from nine different cities between the ages of 18 and 65 years were measured and statistically analyzed. Results: The right articulo-trochanteric distance of all participants was 19.67 ± 4.52 mm and the left articulo-trochanteric distance was 19.10 ± 4.58 mm. The CE angle was 35.11°±7.41° in the right hip and 35.37°±6.76° in the left hip. The acetabular index was 37.58°±5.30° in the right hip and 37.80°±4.82° in the left hip. The collodiaphyseal angle was 138.60°±8.27° in the right and 137.84°±8.01° in the left hip. The prevalence of cross-over sign in the right hip was 6.46% and 6.66% for the left hip. The prevalence of posterior wall sign was 4.24% for the right hip and 4.19% for the left hip. Conclusion: This study has provided prevalence values of cross-over sign, posterior wall sign, acetabular index, collodiaphyseal angle, CE angle and articulo-trochanteric distances of a healthy Turkish population between the ages of 18 and 65 years. Keywords: Acetabulofemoral joint, Adult, Radiography, Acetabular index, Center - edge angle, Articulo-trochanteric distance, Collodiaphyseal angle, Cross - over sign, Posterior wall sign